2017
DOI: 10.1007/s41101-017-0038-y
|View full text |Cite
|
Sign up to set email alerts
|

Water Footprint as an Emerging Environmental Tool for Assessing Sustainable Water Use of the Bioethanol Distillery at Metahara Sugarcane Farm, Oromiya Region, Ethiopia

Abstract: In Ethiopia, sugarcane estate farms and bioethanol distilleries are being expanded at an alarming rate to provide alternative sustainable energy as renewable, affordable, and low carbon footprint bioenergy for the transportation sector. The promotion of bioethanol production is definitely poised to cause high competition for water resources. Thus, the aim of this study was to investigate the water footprint (WF) of sugarcane molasses-based bioethanol production of the Metahara sugarcane farm. Ten years of mete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 31 publications
0
7
0
2
Order By: Relevance
“…Waterlogging condition may lead to a reduction of sugarcane growth and yield (Gomathi et al 2015;Avivi et al 2016;Jaiphong et al 2017). Sugarcane crop water requirement (CWR) defined as the amount of water needed to compensate evapotranspiration process in the field (Fito et al 2017). The value of sugarcane CWR during a crop cycle is within the range of 1,100-1,800 mm, depending on location (Carr & Knox 2011).…”
Section: Irigasi Tetes Permukaan Irigasi Tetes Bawah Permukaan Irigasmentioning
confidence: 99%
“…Waterlogging condition may lead to a reduction of sugarcane growth and yield (Gomathi et al 2015;Avivi et al 2016;Jaiphong et al 2017). Sugarcane crop water requirement (CWR) defined as the amount of water needed to compensate evapotranspiration process in the field (Fito et al 2017). The value of sugarcane CWR during a crop cycle is within the range of 1,100-1,800 mm, depending on location (Carr & Knox 2011).…”
Section: Irigasi Tetes Permukaan Irigasi Tetes Bawah Permukaan Irigasmentioning
confidence: 99%
“…Today, freshwater consumption is increasing rapidly at an unexpected rate due to the fast industrial advancement, world population explosion, mechanized agriculture expansion and progress of civilization (Fito et al 2017a;Fito and Alemu 2019). Basically, in all nations across the globe, access to safe water and sanitation is recognized as a fundamental human right for all (Fito et al 2019a).…”
Section: Introductionmentioning
confidence: 99%
“…The sugarcane WF proc,grey of the plant cane season (CRF: 17.28 m 3 /t, urea: 44.99 m 3 /t) (Table 4) indicated that more than twice the water volume is required to assimilate the pollutant load derived from sugarcane cultivation for urea application to match the water quality standards of the area than for the CRF application. According to Scholten W, 2009, as cited in Fito et al [71], the proportion of the grey WF to the total sugarcane WF in different countries ranges between 4% and 11%. Our obtained results for the plant cane season indicated that the contribution of the grey WF of the CRF treatment to the total WF was 8.98% while that of the urea treatment was 19.27%, more than two times higher than the former.…”
Section: Wf Of Sugarcane Cultivationmentioning
confidence: 99%